IMPLEMENTASI PENGHAPUSAN ASET TETAP DAN ASET TIDAK BERWUJUDSTUDI KASUS PADA BPPKAD KABUPATEN BLORA TAHUN 2019 - Putri Sholiha Anugraini; Siti Puryandani (Magister Manajemen STIE Bank BPD Jateng, 2021)
The process of eliminating Regional Property is one of the series of assets management that is very important and the main. The process can be an indicator of the responsibility of carrying out the duties and functions of the regional apparatus. The money that has been spent into capital goods should be reported accurately and accountably. This type of research is a qualitative research with a case study approach to BPPKAD Blora Regency. This study aims to analyze the process of eliminating regional property and the suitability of the process of elimination with the regulation of regional property management at the BPPKAD Blora Regency. There are 4 (four) indicators of the framework that influence the elimination process, namely the internal control system, regulations, operating standards and procedures as well as human resources. The research data was obtained by in-depth interviews with officials in charge of policy management of goods consisting of the Head of the Asset Division, Head of Sub-Asset and BPPKAD goods management officer. Data was also obtained from field observations in the form of photos or field documentation. The results of data collection are then analyzed and concluded. The results showed that the process of eliminating regional property was not in accordance with the established operating standards and procedures. The results also showed that the process of eliminating regional property in the Blora Regency BPPKAD was in accordance with regulations on the management of regional property. The Blora Regency Government is constrained by the lack of adequate warehouse facilities so that the process of sending goods requires high costs.